A Review of the Efficacy and Safety of Genvoya® (Elvitegravir, Cobicistat, Emtricitabine, and Tenofovir Alafenamide) in the Management of HIV-1 Infection. (April 2018) - Angione, Sara A.; Cherian, Sibyl M.; Özdener, Ayşe Elif
Introduction: This review evaluates the efficacy and safety of Genvoya® (elvitegravir, cobicistat, emtricitabine, and tenofovir alafenamide [EVG/c/TAF/FTC]), a single-tablet regimen used for the management of HIV-1 infection. Phase II and III randomized clinical trials evaluate the efficacy and safety of EVG/c/TAF/FTC and tenofovir disoproxil fumerate (TDF)–containing arms; renal impairment, bone mineral density, metabolic effects, and other adverse events are topics explored within this review. Methods: A MEDLINE with full text and PubMed literature search was conducted for the past 5 years, up to April 2016. Results: Virologic suppression was similar between the EVG/c/TAF/FTC and TDF-containing groups (<50 copies/mL) at week 48. The bone mineral density in the hip and spine showed a significant reduction in the TDF-containing groups. The glomerular filtration rate increased in patients in the EVG/c/TAF/FTC arm and there were significant differences in total proteinuria, albuminuria, and tubular proteinuria in patients switching to EVG/c/TAF/FTC. The most common adverse events were diarrhea, nausea, and headache. Discussion: The coformulated Genvoya regimen is well tolerated and effective in treatment-naive and virologically suppressed patients. Data seem to suggest it may also be effective and safe in patients with mild to moderate renal impairment. The lower-dosed single-tablet regimen has significantly reduced bone and renal side effects.